Research of the Sherabad Epic School Abroad - Kalandarova Dilafruz (International Journal on Integrated Education, 2022)
The article discusses the participation of the well-known American scientist Walter Feldman in folklore field expeditions during his trip to Uzbekistan in the 90s and the comparison of 2 different versions of the meeting scene of Alpomish and Yodgor from the second part of the "Alpomish" saga, "The Return of Alpomish", performed by Kahhor Rahimov. The scientist's observations about the place and relationship of musical notes in the performance of poetic texts related to the episodes of the piece, the influence of space and time on the singing process are analyzed.